Attitude of Dental Clinicians Towards Flexible Dentures: A Questionnaire Survey in Libya - Muftah Elfaidy, Yusra; Abdalla Elnaihoum, Warida; Abdullah Elgotrany, Aseidah (Libyan Journal of Dentistry, 2022)
Background: Management of partially edentulous patients with hard and soft tissue undercuts is complicated, and the use of flexible dentures for these cases offers dual advantages of aesthetics and flexibility. However, research shows a varying preference for flexible dentures among general dental practitioners, prosthodontists, and other dental specialties. Objectives: The aim of this study was to survey the attitude and awareness of a sample of Libyan dental clinicians towards advantages, disadvantages, indications, and contraindications of flexible dentures. Material and methods: A descriptive cross-sectional study was conducted among 250 dentists currently practicing in different cities of Libya. Only 218 dentists responded. Using Google form software, a self-administrable e-questionnaire consisting of thirty-one multiple choice questions with “yes,” “no” or “not sure” answers encompassing major aspects of flexible dentures was conducted through an online survey. Results: Out of 250 Libyan dentists to whom the questionnaire was sent, only 218 dentists responded and our results revealed that the respondents were females more than males with a ratio (2:1) and more than half of them were of age group (35-60 years) work in governmental dental practice with more than ten years of experience and 34.9% of them prefer and often offer flexible dentures to their patients. The majority of respondents with a long-term success of the flexible denture were prosthodontists who had more than ten years of experience with a correct response rate of more than 50% of questions that reflected their attitude and knowledge. Conclusions: Despite the fact that flexible dentures are not taught in Libyan universities of dentistry, about more than one-third of respondents prefer and recommend this treatment to their patients, and the long-term success of these prostheses was dependent on clinicians’ education and their clinical experience.